RELIGIOUS TOLERANCE OF MINANGKABAU AND BATAK ETHNIC STUDENTS IN XAVERIUS BUKITTINGGI HIGH SCHOOL - Arjoni, Arjoni; Charles, Charles; Sari, Intan (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2020)
This article is based on the results of a mini-research that aims to describe the religious tolerance of Minangkabau and Batak ethnic students at Xaverius Bukittinggi High School in the academic year 2019/2020. This research uses a quantitative approach. The steps in this research are conducting preliminary studies, literature studies, data collection, data analysts and conclusions. The population of this study, XII Bukittinggi ethnic group Minangkabau and Batak ethics XII grade students. Sampling with purposive sampling technique. Data collection using a questionnaire, data analysis techniques with normality, homogeneity, and T-test. The results of this study illustrate the religious tolerance of ethnic Minangkabau and Batak students dominated by the tolerant category. There was no significant difference in religious tolerance between ethnic Minangkabau and Batak students. However, differences in religious tolerance scores were found between ethnic Minangkabau students and Batak students on the aspect of maintaining independence in practising religion and respecting the practice of diversity. The Batak students are a minority population in Xaverius Bukittinggi high school while the majority are Minangkabau students population. Development of religious tolerance Students of the Minangkabau ethnic group and the Batak ethnic group at Xaverius High School tend to be equally tolerant and potentially more tolerant when the curriculum and education at the school are carried out properly. The results of this study can be used as consideration for developing religious-spiritual strength counselling and arranging cross-cultural counselling and guidance programs in high schools.